Land use and land cover changes simulated with agent-based modelling for water conservation at catchment scale - Giełda-Pinas Katarzyna; Ligmann-Zielińska Arika; Zwoliński Zbigniew (Limnological Review, 2015)
Various factors influence the spatial and temporal patterns of land cover and land use in lakeland landscapes. Land use/cover change (LUCC) is one of the crucial factors influencing both natural processes that occur in lakelands and lakes and anthropogenic processes, which intensify these changes. Therefore, LUCC at a local and regional scale may be treated as an important geoindicator for the functioning of the lakeland landscape. Nowadays, LUCC mostly depends on different human decisions. In the existing literature, the consequences of negative changes have already been widely recognized. Conversely, in this paper, we focus on the possible positive effects of LUCC. To that end, we built an agent-based model to show how selected human decisions may positively influence lakeland landscapes and lakes. We apply the model to the Gniezno Lakeland, Poland. Based on the environmental decisions of farmers, the model demonstrates how the LUCC pattern may change in time and space and how those changes may influence freshwater quality in four individual lake catchments of the Gniezno Lakeland.